Agroforestry Adoption Decision in Green Growth Initiative Programs: Key Lessons from the Billion Trees Afforestation Project (BTAP) - Ullah, Ayat; Mishra, Ashok K; Bavorova, Miroslava (Environmental management, 2023)
Adoption of agroforestry in the early spring under the green growth initiative programs, such as the Billion Trees Afforestation Project, has positively impacted crop productivity and plantation success in Pakistan. However, the timely adoption decision of agroforestry in the Hindu Kush Himalayan is still low, particularly among smallholders. Using a mixed-method approach, we examine the factors influencing smallholder households and community-level timely agroforestry adoption decisions. Findings show that the early and later decision-makers farmers had agricultural lands on riversides and primarily adopted agroforestry to protect their crops from devastating effects of winds and floods. In contrast, late adoption decision-makers adopted agroforestry for income diversification. Results of our logit model show that several household and community-level factors influence smallholders' timely adoption of agroforestry. The factors that positively affect the timely adoption of agroforestry include age-related factors, education, and the establishment/existence of functional community-based organizations. In contrast, political conflicts and tenure insecurity negatively affect smallholders' timely adoption of agroforestry. In-depth interviews with Village Development Committees members revealed that terrace farming, farms on riversides, communities without access to other energy sources, population growth, and low farm acreage ensured the timely adoption of agroforestry. The policy recommendations include strengthening collaborative efforts among community members, especially engaging educated old-aged farmers (elders of traditional communities) to increase adoption rates and land tenure security to ensure timely agroforestry adoption under the newly launched 10-BTAP.
Keywords: senioři; Farms; příjem; Humans; Agriculture; lidé; Agroforestry; Middle Aged; lidé středního věku; Billion Trees Afforestation Project (BTAP); Income; stromy; zemědělci; Timely adoption; Farmers; zemědělství; Trees; Plantation success; farmy; Aged; Green growth initiative programs